Dynamics of Extreme Rainfall and Its Impact on Forest and Land Fires in the Eastern Coast of Sumatra - Hamdi Akhsan; Muhammad Irfan; Supari; Iskhaq Iskandar (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2023)
This article examines the extreme climate events on the Eastern Coast of Sumatra over four decades (1981-2019) based on the extreme rainfall index defined using the Expert Team on Climate Change Detection and Indices (ETCCDI). The indices used include Consecutive Dry Day (CDD and the total rainfall per year (PRCPTOT). Theses indices were calculated and are based on the daily observation data from eight quality-controlled weather stations. While overall trends in extreme rainfall indices are not significant, there is a noticeable trend towards drought, with CDD rising by 1.23 days per decade and PRCPTOT decreased by 3.16 mm/year. The correlation between the Dipole Mode Index (DMI) and extreme rainfall indices in the August-September-October-November (ASON) period was positive, with CDD increasing with the more positive DMI value. On the other hand, the PRCPTOT index showed a decrease as the DMI more positive. The ENSO index and CDD are positively correlated during the dry season, while ENSO index negatively correlates with PRCPTOT. The duration of CDD during El Niño/positive Indian Ocean Dipole (IOD) events in 1997, 2015, and 2019 had significant impact on the forest and land fires on the Eastern Coast of Sumatra. The results are useful for policymakers in preventing forest and land fires on the Eastern Coast of Sumatra.